Physiological Attributes of Transplant Aman Rice (Cv. Brri Dhan52) as Affected by Tiller Seedlings and Urea Super Granules (Progressive Agriculture, 2014)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, Bangladesh to investigate the effect of age of tiller seedlings, number of tiller seedlings hill-1 and application of urea super granules (USG) on some physiological attributes of transplant Aman rice cv. BRRI dhan52. The experiment consisted of two ages of tiller seedlings viz. 25- and 35-day old, three levels of tiller seedlings hill-1 viz.1, 3 and 5 seedlings hill-1 and three USG levels viz. 0, 1.8g and 2.7g USG per four hills in every alternate row. The experiment was laid out in a randomized complete block design with three replications. The effect of age of tiller seedlings, number of tiller seedlings hill-1 and USG application were significant on crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR) and leaf area index (LAI). The highest CGR and RGR were found by transplanting 35-day old tiller seedlings during the period at 15-30 and 60-75 DAT when 5 tiller seedlings hill-1 were transplanted. The highest NAR was observed at 60-75 DAT with transplanting 5 tiller seedlings hill-1 and the lowest one was recorded at 30-45 DAT. The highest LAI was found at 35-day old tiller seedlings during the period at 60 and 75 DAT when 5 tiller seedlings hill-1 were transplanted. CGR and RGR were found highest by applying 1.8 g USG at 45-60 and 60-75 DAT while NAR was the highest with application of 2.7g USG at 60-75 DAT and lowest one was found in control (0 g USG) at 45-60 and 60-75 DAT. The highest LAI was found by applying 1.8g USG at 15, 30, 45 and 60 DAT and the lowest one was found at 60 DAT in control and at 15, 30 and 45 DAT when 2.7g USG was applied. The highest LAI and CGR were found in older tiller seedlings (35- day old) by transplanting five tiller seedlings hill-1 fertilized with 1.8g USG whereas the highest RGR and NAR were obtained in younger tiller seedlings (25-day old) by transplanting single tiller seedling hill-1 fertilized with 1.8g USG per four hills of every alternate row.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19094 Progress. Agric. 24(1&2): 17 - 27, 2013